Pre-gabi biotic connections between the Americas: an alternative model to explain the “less-splendid isolation” of South America - Agnolin, Federico (2019)
Traditionally, South America was considered as an island continent during most of the Tertiary. However, sparse paleontological and biological evidence indicates that a biotic interchange between North and South America may have been occurred by pre-Pliocene times. Nevertheless, the geological evidence suggesting Miocene closure of the Isthmus is still wanting, and this constitutes an important inconsistency between biological and geological data. With the aim to explain the population of Caribbean islands by terrestrial fauna and flora, several authors proposed that between Eocene and Oligocene times there existed an above-water land span between South America and these islands, currently known as GAARlandia. If this is the case, there must have been biotic interchanges between the Americas and Caribbean islands in a narrow time window. This new hypothesis has deep implications for the understanding of the early phases of the biotic interchange between the Americas by pre-Pliocene times.